Formación un concepto para la acción curricular (2021)
The main objective of any education process is teaching people in all their dimensions, no matter the pedagogic model applied to carry it out. This concept is analyzed in the present article, based on the proposal written by Rafael Flórez in its ontological, teleological, gnoseological, methodological and axiological dimensions, in order to orientate which must be a teaching proposal in the program of Social Communication and Journalism at the Universidad Católica Popular del Risaralda.